Polycystic kidney disease - Hu, Jinghua; Yu, Yong (Biological sciences) (Boca Raton : CRC Press, 2019)
"This volume focuses on methods applied to autosomal dominant polycystic kidney disease (ADPKD), a common human genetic disease. ADPKD is caused by abnormal cilia formation or function. This proposed book will cover the state-of-the-art methods ranging from molecular biology, biochemistry, electrophysiology, to tools in model animal studies"--
OCLC-licensed vendor bibliographic record.
Keywords: Polycystic kidney disease; Polycystic kidney disease -- Genetic aspects; MEDICAL / Endocrinology & Metabolism; MEDICAL / Nephrology; SCIENCE / Life Sciences / Cytology